Religiosity and Spirituality of Personality: A Theoretical and Empirical Comparison of the Concepts - Yaroshchuk, Marianna (Psychological Prospects Journal, 2018)
The article deals with the results of theoretical comparative analysis of religiosity and spirituality phenomena, empirical study of the concept «God», the latter being a basis of primary experience of the investigated phenomena. The goal of the research is theoretical and empirical study of the concepts «spirituality» and «religiosity» as individual features as well as defining common psycho-semantic space of the concepts through free word association test and semantic differential. The author suggested definition of spirituality as an personal search for answers for the question concerning life, sense, transcendental experience that are not necessarily rooted in religious rituals or beliefs of a certain community. Religiosity is understood as an individual feature that envisages the involvement into certain confession on the level of cognitions, emotions, and behavior. Religiosity characterized by ritual, intellectual, experiential, ideological, moral, and cultural dimensions is also determined through religious orientation and immersion in the life contexts. Today’s studies admit non-conformity between religious beliefs, religious behavior, on one hand, and sense of being part of a community. This fact impedes the investigation of religiosity as a universal individual feature and requires taking into account human individual and psychological features. One of the results of the study is the definition of the «God» concept’s associative space that reflects the experience both religious and spiritual. The associative space is represented by the following main categories: subjects (creator, almighty, owner, father, spirit, savior), emotional and sensual sphere (love, good, faith), and societal and human values (justice, truth, help, religion). Finally, connotative meanings of the investigated concept were defined and its psycho-semantic space was built.